Digital financial inclusion's impact on farmers' income and spatial spillover effects: Evidence from inner Mongolia, China - Hua Li; Xue Wei; Wenhui Chen (Heliyon)
This study analyzes data from 12 prefecture-level cities in the Inner Mongolia Autonomous Region from 2011 to 2022 to investigate how digital financial inclusion(DFI) affects the increase in farmers' incomes and its spatial spillover effects. The Dagum Gini coefficient indicates that disparities in DFI development are primarily due to inter-regional differences. Using the Spatial Durbin Model, based on an economic distance matrix, the study finds that DFI strongly promotes income growth for farmers. Moreover, it reveals that the spatial spillover effects of DFI have a greater impact on increasing farmers' incomes than the direct effects of inclusion itself.